Multipotent mesenchymal stromal cells are sensitive to thermic stress – potential implications for therapeutic hyperthermia. (1st January 2020) - Rühle, Alexander; Thomsen, Andreas; Saffrich, Rainer; Voglstätter, Maren; Bieber, Birgit; Sprave, Tanja; Wuchter, Patrick; Vaupel, Peter; Huber, Peter E.; Grosu, Anca-Ligia; Nicolay, Nils H.
Abstract: Purpose: Hyperthermia demonstrated clinical efficacy in multimodal cancer treatment. Multipotent mesenchymal stromal cells (MSCs) as part of the tumor-supporting stroma modulate tumor response and tissue regeneration after hyperthermia. We aimed to investigate the effects of hyperthermia on the survival, stem cell characteristics and heat shock expression of human MSCs. Materials and methods: Human MSCs and normal human dermal fibroblasts (NHDFs) were exposed to temperatures between 37 °C and 44 °C for 60 min, and hyperthermic sensitivity was examined by clonogenicity, proliferation and viability assays. The influence of 42 °C hyperthermia on the MSCs' adhesion potential, migratory capacity, surface marker expression and multi-lineage differentiation capability was investigated. Cell cycle distribution, apoptosis and senescence after 42 °C hyperthermia were determined by flow cytometry and β-galactosidase staining. Heat shock protein expression was determined by Western Blots. Results: MSCs exhibited decreased clonogenic survival after 40 °C and 42 °C hyperthermia compared to NHDFs, while proliferative activity and viability were comparable after hyperthermia up to 44 °C. MSC adhesion was reduced after 42 °C hyperthermia, while the characteristic surface marker expression and the migratory ability remained unaffected in 42 °C hyperthermia-exposed MSCs. 42 °C hyperthermia diminished the adipogenic differential potential of all tested MSC samples. A pronounced G2/M arrest was found after 42 °C hyperthermia and was associated with increased apoptosis and senescence levels in MSCs. MSCs exhibited slightly lower heat shock protein levels compared to NHDFs. Conclusion: Human MSCs exhibit a thermosensitive phenotype which reduced the multipotent cells' regenerative abilities, resulting in impaired tissue regeneration after hyperthermia treatment or thermal injuries. On the other hand, tumor-associated MSCs may be efficiently targeted by hyperthermia treatment.